Establishment of a lethal mouse model of emerging tick-borne orthonairovirus infections - Ariizumi, Takuma; Tabata, Koshiro; Itakura, Yukari; Kobayashi, Hiroko; Hall, William W.; Sasaki, Michihito; Sawa, Hirofumi; Matsuno, Keita; Orba, Yasuko (PLoS pathogens, 2024)
Emerging and reemerging tick-borne virus infections caused by orthonairoviruses (family Nairoviridae ), which are genetically distinct from Crimean-Congo hemorrhagic fever virus, have been recently reported in East Asia. Here, we have established a mouse infection model using type-I/II interferon receptor-knockout mice (AG129 mice) both for a better understanding of the pathogenesis of these infections and validation of antiviral agents using Yezo virus (YEZV), a novel orthonairovirus causing febrile illnesses associated with tick bites in Japan and China. YEZV-inoculated AG129 mice developed hepatitis with body weight loss and died by 6 days post infection. Blood biochemistry tests showed elevated liver enzyme levels, similar to YEZV-infected human patients. AG129 mice treated with favipiravir survived lethal YEZV infection, demonstrating the anti-YEZV effect of this drug. The present mouse model will help us better understand the pathogenicity of the emerging tick-borne orthonairoviruses and the development of specific antiviral agents for their treatment.